Madrasah 5.0: Sinergi Nilai Islam, Kecerdasan Buatan, dan Manajemen Partisipatif - Dwiyama, Fajri (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This article aims to explore the transformation model of madrasah management through the integration of Islamic values, artificial intelligence (AI), and participatory management in responding to the challenges of Society 5.0. Using the systematic literature review (SLR) method, this study analyzed 45 selected publications from the Scopus database, ERIC, and Islamic education journals (2018–2023). The results of the study show that the concept of "Madrasah 5.0" can be realized through three main pillars: (1) humanist technology based on the principles of tawhid and adab, (2) collaborative governance that adopts digital sura, and (3) AI-based continuous evaluation system to maintain the harmony of Islamic values. Key challenges include cultural resistance, limitations of digital infrastructure, and the risk of technological reduction in spiritual value. This article recommends strengthening AI literacy, developing open source participatory platforms, and revising madrasah management policies by the Ministry of Religion of the Republic of Indonesia.